Accuracy of virtual assessment in hand trauma. (March 2022) - Westley, S.; Mistry, R.; Dheansa, B.
Summary: A virtual clinic was developed from an existing telemedicine system to manage hand trauma in the Queen Victoria Hospital, East Grinstead, UK, during the first wave of the COVID-19 pandemic. This study evaluates the accuracy of the assessments made and makes comparisons to the traditional face-to-face clinic. The accuracy of assessment was analysed by comparing diagnosis with findings at surgery. One hundred and eighty-nine virtual assessments conducted by telephone with photographic data or by video were compared to 129 face-to-face assessments conducted prior to the pandemic. There was no difference in the accuracy of virtual and face-to-face clinics for patients treated surgically (p=0.27); treatment was correctly predicted for 87% of the virtual group and 78% of the face-to-face group. However, fewer virtual assessments led to a surgical outcome (p=0.0064); 68% of the virtual group had surgical outcomes compared to 82% of the face-to-face group. Most face-to-face assessments were done by a specialty trainee compared to a range of clinicians in the virtual clinic. Accuracy of assessment among trainees was significantly associated with experience for the virtual (p=0.045) but not face-to-face clinics (p=0.94). Virtual assessment by video versus telephone plus photographs were similarly accurate. We conclude that virtual triage serves as a successful alternative to face-to-face appointments. It is robust and succeeds in reducing footfall to the hospital site in line with recent social distancing measures against COVID-19. We have shown that video conferencing triage is no better than telemedicine triage with telephone and photographs.